Breast cancer survivorship symptom management: current perspective and future development. (January 2013) - van Londen, G; Beckjord, EB; Dew, MA; Cuijpers, P; Tadic, S; Brufsky, A
SUMMARY Increasing numbers and longevity of cancer survivors has furthered our insight into the factors affecting their health outcomes, suggesting that multiple factors play a role (e.g., effects of cancer treatments and health behaviors). Emotional and physical symptoms may not always receive sufficient attention. In this short narrative review highlighting recent literature, we describe the most common physical and emotional symptoms of breast cancer survivors aged 50 years and older and outline a multidisciplinary symptom management approach, regardless of symptom etiology.